PENGEMBANGAN BAHAN AJAR ANATOMI TUMBUHAN UNTUK MENUNJANG LITERASI KUANTITATIF MAHASISWA BIOLOGI - Andriansyah, Ryan (2014)
Biologi abad 21 diharapkan berkembang ke arah sains kuantitatif. Namun, literasi kuantitatif pada mata kuliah anatomi tumbuhan belum menonjol. Sebagai upaya memenuhi kebutuhan tersebut dilakukanlah pengembangan bahan ajar anatomi tumbuhan untuk menunjang literasi kuantitatif mahasiswa biologi dengan mengacu kepada indikator literasi kuantitatif. Metode penelitian ini adalah penelitian pengembangan dengan objek penelitiannya adalah buku petunjuk praktikum yang berisi teori dan LKM terintegrasi pada konsep parenkim dan batang. Uji coba dilakukan kepada 30 mahasiswa S1 yang sedang mengontrak anatomi tumbuhan. Hasil penelitian menyatakan bahan ajar ini dapat meningkatkan nilai literasi kuantitatif N-gain 0,60 (sedang) dengan kontribusi 24,21% yang diduga berasal dari bahan ajar hasil pengembangan. Biology in the 21st century is expected to evolve into a quantitative science. However, plant anatomy course material is still not support the development of quantitative literacy. In an effort to meet the need of quantitative literacy, this research has been conducted on plant anatomy teaching materials to improve the quantitative content. Quantitative content in the teaching material refers to the indicators of quantitative literacy. This method is a research and development with the object of research is teaching material that contains theory and practical guide. The material selected is parenchymal tissue and stem organ. The trial was conducted to 30 undergraduate students who are taking plant anatomy class. The results showed that the developed teaching materials can increase the score of quantitative literacy that can be seen from N-gain of 0.6 (medium category). Score of plant anatomy quantitative literacy was contributed about 24.21% to value of general quantitative literacy. Keyword: plant anatomy teaching material, quantitative literacy